2022
DOI: 10.1042/cs20220261
|View full text |Cite
|
Sign up to set email alerts
|

CGP42112: the full AT2 receptor agonist and its role in the renin–angiotensin–aldosterone system: no longer misunderstood

Abstract: For years, the AT2R-selective ligand CGP42112 has been erroneously characterized as a partial agonist, partly due to its ability to also interact with the AT1R at high concentrations. As late as 2009, it was still being characterized as an antagonist as well. In this perspective/opinion piece, we try to resolve the ambiguity that surrounds the efficacy of this compound by extensively reviewing the literature, tracing its beginnings to 1989, showing that CGP42112 has never been convincingly shown to be a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Since the analgesic effects of Ang II and III are suppressed by AT1 receptor and AT2 receptor antagonist losartan and CGP42,112A, respectively, it could be concluded that both receptors are involved. However, it has been suggested that CGP42,112A may be a full agonist of the AT2 receptor [18], indicating the need for further studies on the specific role of AT2. Since losartan exacerbated incision-induced allodynia even when administered alone [16], it could be concluded that endogenous local Ang-producing system works in the analgesic direction in PAG via AT1 receptors (Figure 2).…”
Section: Spinal Cordmentioning
confidence: 99%
“…Since the analgesic effects of Ang II and III are suppressed by AT1 receptor and AT2 receptor antagonist losartan and CGP42,112A, respectively, it could be concluded that both receptors are involved. However, it has been suggested that CGP42,112A may be a full agonist of the AT2 receptor [18], indicating the need for further studies on the specific role of AT2. Since losartan exacerbated incision-induced allodynia even when administered alone [16], it could be concluded that endogenous local Ang-producing system works in the analgesic direction in PAG via AT1 receptors (Figure 2).…”
Section: Spinal Cordmentioning
confidence: 99%
“…In vascular smooth muscle cells (VSMCs), Ang II binds to AT1R, activating phospholipase C and raising intracellular [Ca +2 ], leading to vasoconstriction [3,4]. Activating AT2R, Ang II lowers blood pressure by vasodilatation and nitric oxide (NO) release [11]. Also, AT2R is involved in wound healing and tissue remodeling [12].…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%